Leadership styles and organizational performance:|bThe impact of gender - Ngu, Nguok Ying. (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The general objective of this study was to examine the gender differences in leadership behaviour and investigate the impacts of leadership behaviour on organizational performance of Sibu-based companies. while researchers have discovered the relationship between the leadership behaviour and organizational performance and understand about the impact of the leadership behaviour on the organizational performance of Sibu-based companies. In addition, researches also have discovered gender difference in leadership behaviour, the possible reason and explanation for the findings. Hence, the present research differs from the previous studies where a comprehensive study's framework has allowed for a better understanding on these differences and relationships.